THE INFLATION - UNEMPLOYMENT NEXUS IN THE LIGHT OF GLOBALIZATION AND ECONOMIC OPENNESS - Koziuk, Viktor (Journal of European Economy, 2018)
The paper outlines important globalization-related changes in the macro-economic sphere on the basis of empiric analysis of the relationship between inflation and unemployment in the most developed countries. The discovered lack of feedback between inflation and unemployment served as a basis for proving, in the course of the last century, that, according to theoretical suppositions, the monetary policy becomes more neutral, which makes it impossible to increase the natural level of employment at the cost of factors that stimulate aggregate demand. The interdependence between inflation and unemployment varies for large and small countries. For the G-7 countries, the stagflationary interdependence between inflation and unemployment is normal; for the small open economies of OECD, this interdependence differs from the one described by the Philips curve, and it is not stagflationary. The author concludes that this situation is conditioned by differing abilities of small open economies to react to production and employment shocks in view of their higher degree of openness and sensitivity to financial upheavals.